2020
DOI: 10.1021/acs.inorgchem.0c00567
|View full text |Cite
|
Sign up to set email alerts
|

A 2-Fold Interpenetrated Nitrogen-Rich Metal–Organic Framework for Rapid and Selective Adsorption of Congo Red

Abstract: A new metal−organic framework was prepared based on a mixed ligand system of the designed nitrogen-rich 3,6bis(2-methylimidazole)pyrimidine (b2mpm) and benzophenone 4,4′-dicarboxylic acid (H 2 bpndc). The prepared material shows a three-dimensional 2-fold interpenetrated pcu framework and features rectangular channels decorated with nitrogen sites. Thanks to the abundant hydrogen bonding and π−π stacking interactions, the titled material can rapidly adsorb Congo red (CR) and presents ultrahigh adsorption capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…The pore size and charge of MOF adsorbents remarkably affect the selective adsorption of organic dyes. Among MOF materials, ionic MOFs with precise adoption of metal and ligands could achieve the tuning of pore sizes and carried charges for effective adsorption of targeted dyes. Nevertheless, other influencing factors including solvent effect effecting this separation process based on ion exchange and size exclusion as a chromatography method are scarcely studied.…”
Section: Introductionmentioning
confidence: 99%
“…The pore size and charge of MOF adsorbents remarkably affect the selective adsorption of organic dyes. Among MOF materials, ionic MOFs with precise adoption of metal and ligands could achieve the tuning of pore sizes and carried charges for effective adsorption of targeted dyes. Nevertheless, other influencing factors including solvent effect effecting this separation process based on ion exchange and size exclusion as a chromatography method are scarcely studied.…”
Section: Introductionmentioning
confidence: 99%
“…The peak at 1633 cm –1 of the CO vibration shifted to 1600 cm –1 , and the peak at 1397 cm –1 of the C–N bending vibration shifted to 1364 cm –1 . A new adsorption band appeared at 1423 cm –1 (−NH 2 bending vibration) of CR@ 1a , which might be ascribed to the hydrogen bond between CO of 1a and the −NH 2 groups of CR. , In addition, a π–π packing interaction might exist between 1a and CR – bearing more aromatic rings, which contributes to the adsorption of CR – . , …”
Section: Results and Ciscussionmentioning
confidence: 99%
“…38,39 In addition, a π−π packing interaction might exist between 1a and CR − bearing more aromatic rings, which contributes to the adsorption of CR − . 40,41 3.4. CO 2 Adsorption Properties.…”
Section: Results and Ciscussionmentioning
confidence: 99%
“…119,124,125 Recent results show that ZJU-48 and {[Zn 4 (bpndc) 4 (b2mpm) 2 ]Á2DMFÁ 4H 2 O} can also be good adsorbents for various dyes (MO, RhB, MB, and NR) with high removal capacity. 126,127 Shahid et al have developed a copper-based MOF [{Cu (bipy) 1.5 (H 2 -pdm)}Á2NO 3 ÁH 2 O] n (Cu-MOF-1) for the adsorptive removal of MB, MO and RhB from wastewater effluents. The adsorption mechanism for adsorptive removal of MB, MO and RhB from wastewater effluents showed that the interaction between the MOF and dyes is mainly due to p-p stacking, electrostatic interactions and H-bonding (Fig.…”
Section: Adsorption Through Mofsmentioning
confidence: 99%